Side by Side with People : Korea's Experience on Participatory Auditing - Kim, Seongjun (World Bank Group, Washington, DC, 2015)
The Board of Audit and Inspection of Korea (hereinafter referred to as BAI) has gradually expanded the dimensions of its cooperative relationship with the citizenry since its establishment. The BAI has gone through the information and consultation stages and has now reached the stage of partnership for decision-making with citizens.1 The BAI takes advice on its audit direction and formally receives audit requests from the citizens. In addition it takes tips on fraud, waste, or mismanagement of public funds along with civil petitions and complaints from the citizens. The BAI also makes all audit reports available to the citizenry through its website. The fact that the BAI annually receives over ten thousand petitions or complaints from the citizenry and the business community well reflects the significance of this cooperative relationship. The BAI also receives about 200 audit requests per year from Korea s citizens. This paper addresses three key issues associated with the Supreme Audit Institution (SAI) s engagement with citizens based on the BAI s varied cooperation experiences with citizens: i) the values and benefits of SAI s engagement with citizens; ii) the potential risks; and iii) practical approaches to ensure the identified values and benefits while controlling the risks.